PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) DANADVERSITY QUOTIENT TERHADAP HASIL BELAJAR PADA MATERIPOKOK FLUIDA STATIS DI KELAS XISEMESTER II SMA NEGERI 6 BINJAI T.P. 2015/2016 - Fajrianti, Ferawati; Sani, Ridwan Abdullah (Universitas Negeri Medan, 2016)
This research aimed to know the effect of using guided inquiry learning model and adversity quotient against the studentsâ achievement on the statistic fluid material for XI grade-second year students in SMA Negeri 6 Binjai Academic Year 2015/2016. The kind of this research was quasi experiment. The research population was the whole students in the XI grade for the second semester in SMA Negeri 6 Binjai which consisted of three classes. The way to take a research sample used cluster random sampling by taking 2 classes from 3 classes randomly so that finding XI-IPA 1 class as an experiment class which amounted 45 students and XI-IPA 3 class as a control class which had 45 students. There were two instruments used for this research, they are; 1) achievement test in the form multiple choice with the amunt of 20 questions which the validators had stated valid for the test; 2) adversity quotient observation sheet which consisted of 20 questions which had been stated valid by the validators and 3) achievement activity observation sheet. For testing the hypothesis used ANAVA two-lanes test 2x2. On this research design used high adversity quotient devision and low adversity quotient. The result of testing the hypothesis used ANAVA with SPSS 16.0 gained on the use of guided inquiry model and conventional model gained a significant standard of quality 0.000 so the hypothesis could be acceptable because the guided inquiry learning model had a better result than conventional learning model. It could be concluded that there was no correlation between model and adversity qoutient. So, it could be concluded that students who had high adversity quotient would gain a good achievement.